Comparison of sexual behaviour, drvg use and std-aids beiween adolescents from a private and public sciknn in São Paulo, Brazil - Strazza, Leila; Azevedo, Raymundo S.; Carvalho, Heráclito B.; Massad, Eduardo (Brazilian Journal of Sexually Transmitted Diseases, 2003)
[...]